Theory Versus Practice in Risk Analysis: A Reply. - Greer, Willis R.; Skekel, Ted D. (The Accounting Review, 1975)
Abstract This article presents response of the author on the comments made by scholar C.G. Hoskins on the paper "Theory Versus Practice in Risk Analysis: An Empirical Study," that was published in the July 1974 of the periodical "The Accounting Review." The comment by Hoskins represents a significant advance in modeling actual decision processes. However, one must add that Hoskins' findings support rather than dispute the conclusion of the original study that there appears to be substantial conflict between the decision processes used by actual decision makers and existing utility theory. The author's intentions in writing this response are to demonstrate why this is so and to expand further on the Hoskins model. It was restated that the model in the original study was not designed to produce decisions, which closely paralleled actual decisions. Rather, the model was built in the shape of classical utility theory with parameters, which were computed from an explicit statement by the firms as to their attitude toward risk-taking. The principal conclusion of the original research was that actual decisions are inconsistent with such a model.